A historical exposition of women led churches in Zimbabwe: a case of Guta Ramwari church - Redzo, Ratidzo (Midlands State University, 2017)
This dissertation seeks to examine and analyse the historical explanation of women led churches in Zimbabwe tracing from GutaRaJehovah which was formed by Mai Chaza in 1954. The study portrays that the church grew during the colonial era where patriarchy was dominant and suppression of women was rampant and were restricted to many sorts of life. The church expanded because of healing practices which were performed in the church, it became popular to many African countries and abroad. This is an empirical study which used in-depth interviews, observation method to both men and women of G.R.M and former members and other secondary sources. Objectives of the study were to explore the growth of G.R.M during colonial administration, to have a close look on how women churches rose and the acceptance by the society. Also to analyse the works by Mai Chaza through faith healing and its contribution the rise of women churches. The study found out that G.R.M managed to break the chains of patriarchy in colonial set-up as she attained the tittle ‘faith healer’ and prophetess leading an independent church. It reveals also that women now play vital roles in the church as prophetesses. Other finding shows the challenges which emerged after the death of Mai Chaza and power dynamics took place. The study claims that women have broken from the shells except in some AICs like JMAC where women are submissive and humble at home and at church and their voices are not heard.